Reconan FEA, User's Manual, v2.00 - Markou, George; Mourlas, Christos (My University, 2020)
It is well known that every FEM program consists of three different parts. The first and the third parts are those that deal with the visualization of the FEM model and the results that the second part produces. Meaning that we have a pre– and post– processing program (first and third part respectively) for the creation (mesh generators, renumbering etc.) and visual illustration of FEM arithmetic models (nodes, elements, material etc.) and results (stress, strain, displacements etc.). For the arithmetic analysis procedure we need a FEM solver which is the one responsible for the interpretation of the FEM mesh geometry into the final arithmetical model which will be solved by using the required solution strategy. After the arithmetic interpretation, the FEM solver will use the appropriate solution procedure in order to generate the required results through the solution of the model. For the creation and the visual representation of ReConAn FEM models, an interface was developed that gives ReConAn the ability to read all required FEM information from a neutral text type file that Femap v9.0 produce. Femap provides comprehensive functionality in an independent environment for modeling, simulation and review of product performance results. Geometry creation; Import or export of several file types; Meshing; User interface; Results; API. ReConAn uses two post-processing programs. The first one is Femap, which provides all necessary post-processing tools that a FEM code should have, such as stress and strain contouring, virtual animation etc. The second post-processing program is ReConAn Eye which is encapsulated inside ReConAn main code structure. ReConAn Eye is based on pre-build OpenGL libraries f90gl. f90gl is a public domain implementation of the official Fortran 90 bindings for OpenGL. OpenGL is the industry's most widely used, supported and best documented 2D/3D graphics API making it inexpensive & easy to obtain information on implementing OpenGL in hardware and software. The need for the creation of a second post-processor lied within the inability of Femap to illustrate discontinuities (cracks). One of the material models that ReConAn includes in its material libraries, is that of the 3D smeared crack material model. The smeared crack approach gives the arithmetic ability of modeling materials that are dominated by crack phenomena such as concrete. Due to the fact that Femap cannot illustrate 3D cracks at a Finite Elements gauss point, the development of a visual tool that could do so was necessary. ReConAn Eye has the ability of 3D crack visualization in addition to its basic abilities (3D graphical FEM model illustration, deformations - animation). The generic code of ReConAn is written in Fortran 90/95 language and the development was done with the use of Microsoft Visual Studio. The latest Intel Fortran Compiler was used for the build of the final product (Release Configuration). ReConAn FEA v2.00 was built to run in Windows XP, Vista and 7 for 64bit CPU systems. ReConAn code requires further numerical testing in order to configure its numerical advantages in correlation with other software packages. Nevertheless, all numerical research that were conducted for this reason, showed that ReConAn combines numerical robustness and efficiency.